2019
DOI: 10.1016/j.molcel.2019.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Related Hormones Induce Apoptosis by Stabilizing Schlafen-12 Protein Turnover

Abstract: The mitochondrial pathway of apoptosis is controlled by the ratio of anti-and pro-apoptotic members of the Bcl-2 family of proteins. The molecular events underlying how a given physiological stimulus changes this ratio to trigger apoptosis remains unclear. We report here that human 17-b-estradiol (E2) and its related steroid hormones induce apoptosis by binding directly to phosphodiesterase 3A, which in turn recruits and stabilizes an otherwise fast-turnover protein Schlafen 12 (SLFN12). The elevated SLFN12 bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 24 publications
(32 reference statements)
7
80
1
Order By: Relevance
“…As expected, analysis of the response to estrogen in the sensitive HeLa cells revealed a significant increase in p53, pRb, γh2AX, and PARP1 cleavage (Figure 5A, top panel). Confirming the previously observed increase in apoptosis following estrogen in HeLa cells(23). Furthermore, analysis in the HPV-cancer cells reveals no dramatic alterations in p53, pRb, or PARP1 cleavage; however, there is a significant increase in γh2AX in C33a cells (Figure 5A, middle panel).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…As expected, analysis of the response to estrogen in the sensitive HeLa cells revealed a significant increase in p53, pRb, γh2AX, and PARP1 cleavage (Figure 5A, top panel). Confirming the previously observed increase in apoptosis following estrogen in HeLa cells(23). Furthermore, analysis in the HPV-cancer cells reveals no dramatic alterations in p53, pRb, or PARP1 cleavage; however, there is a significant increase in γh2AX in C33a cells (Figure 5A, middle panel).…”
Section: Resultssupporting
confidence: 90%
“…However, it soon became clear that our initial hypothesis was incorrect when HPV+ cells were specifically sensitized via estrogen treatment, while HPV-cells showed little to no response. We were also extremely surprised with the dramatic response to estrogen that we observed in HeLa cells, although recently published data now confirms our observations(23). This recent study utilizing HeLa cells as a model to analyze steroid signaling confirmed these cells are particularly sensitive to estrogen.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations